Prognostic value of dynamic hypoxia PET in head and neck cancer: results from a planned interim analysis of a randomized phase II hypoxia-image guided dose escalation trial ; parts of this work were presented at the Meeting of the European Society for Therapeutic Radiology and Oncology (ESTRO 33), Vienna, Austria, 4-8th April 2014 - Welz, Stefan; Alber, Markus (Radiotherapy and oncology, 2017)
Background and purpose: To prospectively assess the prognostic value of tumour hypoxia determined by dynamic [18F]Fluoromisonidazole (dynFMISO) PET/CT, and to evaluate both feasibility and toxicity in patients with locally advanced squamous cell carcinomas of the head and neck (LASCCHN) treated with dynFMISO image-guided dose escalation (DE) using dose-painting by contours. Patients and methods: We present a planned interim analysis of a randomized phase II trial. N=25 patients with LASCCHN received baseline dynFMISO PET/CT to derive hypoxic volumes (HV). Patients with tumour hypoxia were randomized into standard radiochemotherapy (stdRT) (70Gy/35 fractions) or DE (77Gy/35 fractions) to the HV. Patients with non-hypoxic tumours were treated with stdRT. Loco-regional control (LRC) in hypoxic patients randomized to stdRT was compared to non-hypoxic patients. Feasibility and toxicity were analysed for patients in the DE arm and compared to stdRT. Results: With a mean follow-up of 27months, LRC in hypoxic patients receiving stdRT (n=10) was significantly worse compared to the non-hypoxic group (n=5) (2y-LRC 44.4% versus 100%, p=0.048). The respective LRC for the DE group (n=10) was 70.0%. Treatment compliance as well as acute and late toxicity did not show significant differences between the DE and the standard dose arms. Conclusion Tumour hypoxia determined by baseline dynFMISO PET/CT is associated with a high risk of local failure in patients with LASCCHN. First data suggest that DE to HV is feasible without excess toxicity.